Minimal inter-particle distance in atom clusters - Vinkó, Tamás (Acta Cybernetica, 2005)
A general method for obtaining minimal interatomic distance in molecule conformation problems is introduced. The method can be applied to a wide family of potential energy functions having reasonable properties. Using this method new lower bounds for the minimal inter-particle distance for the optimal Lennard-Jones and Morse potential functions are derived which are independent from the number of atoms. Improved linear lower bounds for the optimal function values for Lennard-Jones and Morse potentials are also given.